PENGARUH AKUNTABILITAS, KOMITMEN PERANGKAT DESA DAN PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN DANA DESA DI KECAMATAN BESUKI - Saputri, Vilda; Tohari, Amin; Widiawati, Hestin Sri (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to determine the accountability, commitment of village officials and community participation partially or simultaneously influence the management of village funds. The population used in this study were all villages in Besuki District, which amounted to 10 villages. The sample used in this study amounted to 73 respondents. Collecting data in this study using purposive sampling. And the research method used is associative quantitative methods, namely testing validity, reliability, classical assumptions, multiple linear regression analysis, hypotheses and coefficients of determination with the SPSS 23 program. village and community participation in the management of village funds. However, both accountability, commitment from village officials and community participation have a simultaneous effect on the management of village funds. So it is hoped that the village government in managing village funds must be carried out properly in order to realize the principle of good government in its implementation.